The European wars of religion an interdisciplinary reassessment of sources, interpretations, and myths - Palaver, Wolfgang 1958-; Rudolph, Harriet; Regensburger, Dietmar (Ashgate, 2016)
"In recent years religion has resurfaced amongst academics,in many ways replacing class as the key to understanding Europe's historical development. This has resulted in an explosion of studies revisiting issues of region,confessional violence and holy war during the early modern period. But the interpretation of the European wars of religion still remains constrained by national boundaries, tied into the process of state building as well as nation building. In order to untangle this complex web and more thoroughly interrogate these concepts and assumptions, this volume focusses on terms repeatedly used and misused in public debates such as 'religious violence' and 'holy warfare' within the context of military conflicts labelled 'religious wars'. The chapters not only focus on the role of religion, but also on the emerging state as a driver of the escalation of violence in the age of religious war"